Effect of 1-week betalain-rich beetroot concentrate supplementation on cycling performance and select physiological parameters - Mumford, P. W.; Kephart, W. C.; Romero, M. A.; Haun, C. T.; Mobley, C. B.; Osburn, S. C.; Healy, J. C.; Moore, A. N.; Pascoe, D. D.; Ruffin, W. C.; Beck, D. T.; Martin, J. S.; et al. (European Journal of Applied Physiology, 2018)
Purpose: Betalains are indole-derived pigments found in beet root, and recent studies suggest that they may exert ergogenic effects. Herein, we examined if supplementation for 7 days with betalain-rich beetroot concentrate (BLN) improved cycling performance or altered hemodynamic and serum analytes prior to, during and following a cycling time trial (TT). Methods: Twenty-eight trained male cyclists (29 ± 10 years, 77.3 ± 13.3 kg, and 3.03 ± 0.62 W/kg) performed a counterbalanced crossover study whereby BLN (100 mg/day) or placebo (PLA) supplementation occurred over 7 days with a 1-week washout between conditions. On the morning of day seven of each supplementation condition, participants consumed one final serving of BLN or PLA and performed a 30-min cycling TT with concurrent assessment of several physiological variables and blood markers. Results: BLN supplementation improved average absolute power compared to PLA (231.6 ± 36.2 vs. 225.3 ± 35.8 W, p = 0.050, d = 0.02). Average relative power, distance traveled, blood parameters (e.g., pH, lactate, glucose, NOx) and inflammatory markers (e.g., IL-6, IL-8, IL-10, TNFa) were not significantly different between conditions. BLN supplementation significantly improved exercise efficiency (W/ml/kg/min) in the last 5 min of the TT compared to PLA (p = 0.029, d = 0.45). Brachial artery blood flow in the BLN condition, immediately post-exercise, tended to be greater compared to PLA (p = 0.065, d = 0.32). Conclusions: We report that 7 days of BLN supplementation modestly improves 30-min TT power output, exercise efficiency as well as post-exercise blood flow without increasing plasma NOx levels or altering blood markers of inflammation, oxidative stress, and/or hematopoiesis.